Boundary bound states in the Bose–Hubbard-like chain - Zvyagin, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The degenerate Hubbard-like chain with open boundary conditions is studied with the help of the Bethe ansatz. The special case of the Bose–Hubbard-like chain is studied in detail. Boundary bound states, which appear as the consequence of the local potential(s), applied to the edge(s) of the open chain are studied in the ground state.